Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Karyawan - Ahmad Rivai (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this study was to determine and analyze the effect of transformational leadership on employee performance at PT Federal International Finance - Medan, to determine and analyze the influence of organizational culture on employee performance at PT Federal International Finance - Medan and to determine and analyze the influence of transformational leadership and organizational culture. on employee performance at PT Federal International Finance - Medan. The population of this study were all 60 permanent employees of PT Federal International Finance-Medan. The data analysis technique used is multiple regression. The results of this study indicate that partially transformational leadership and organizational culture have a positive and significant effect on the performance of employees of PT Federal International Finance - Medan and that transformational leadership and organizational culture simultaneously have a positive and significant effect on the performance of employees of PT Federal International Finance – Medan.